Politics and leadership in global health delivery: lessons from South Africa's HIV and health insurance initiatives - Amy Madore, MPA; Julie D Rosenberg, MPH; Hisham Yousif, MD; Chris Desmond, PhD; Rebecca L Weintraub, MD (Elsevier, 2017)
Background: South Africa's Health Minister Aaron Motsoaledi inherited an HIV epidemic and a weak public health system when he took office in 2009. His priorities were to establish a national programme to address HIV and to create a system of national health insurance (NHI) to increase access to affordable and high-quality health care. By 2015, Motsoaledi's work on HIV was considered as a success; however, work on the creation of NHI was stymied. Here, we aimed to compare the design, promotion, and implementation of the national HIV programme-a primarily vertical programme-with that of NHI, a horizontal programme. Methods: In January and February, 2015, we conducted 20 semi-structured interviews in South Africa with government leaders, civil society, researchers, health-care practitioners, private insurers, and international non-governmental organisations. We analysed interviews and available quantitative data from government, academic, and industry sources and distilled key themes in two teaching cases. Findings: We identified several key differences between the HIV programme and NHI efforts, including the role that leadership and politics play in health policy and care delivery; the effect of historical, economic, and cultural context on outcomes and leaders' ability to institute change; and the importance of strategy in planning and decision making. We noted both contextual barriers (such as public distrust of government) and catalysts (demand for HIV treatment) in the programmes. Furthermore, the approach used by the Minister of Health sometimes hindered programme success (for example, the exclusion of private insurers from NHI design) and sometimes enabled success (such as the engagement of civil society in the HIV response). For both programmes, the availability or absence of outcomes data affected the Minister's ability to advocate for change and to make strategic decisions about how to invest in health. Interpretation: The comparison of South Africa's well known and effective HIV programme with its stalled NHI efforts-both led by the same person with very different results--sheds light on important considerations when approaching complex, large-scale change. Our analysis of the politics of health systems shows how explicit acknowledgement of the political nature of health will lead to more effective health promotion strategies and policies. Political leaders can either drive or hinder the implementation of evidence-based public health practices. Funding: The Ministerial Leadership in Health Program of the Harvard TH Chan School of Public Health, and Children's Investment Fund Foundation (CIFF), UK.